Correction: Ultrasound-assisted leaching of vanadium from fly ash using lemon juice organic acids. Issue 63 (19th October 2020) - Rahimi, G.; Rastegar, S. O.; Rahmani, F.; Gu, T.
Abstract : Correction for 'Ultrasound-assisted leaching of vanadium from fly ash using lemon juice organic acids' by G. Rahimi et al., RSC Adv., 2020, 10, 1685–1696, DOI: ; 10.1039/C9RA09352G .